The Influence of Work Motivation and Organizational Commitment on Organizational Citizenship Behavior (OCB) in RRI Bandar Lampung Employees - Aisyah Rizqa Ayundra; Yuningsih Yuningsih (International Forum of Researchers and Lecturers, 2025)
Motivating human resources is essential for enhancing organizational performance and achieving company objectives. This study explores the influence of work motivation and organizational commitment on organizational citizenship behavior among employees at RRI Bandar Lampung. Data were collected through a Likert-scale questionnaire from 84 respondents and analyzed using multiple linear regression. The findings support the first hypothesis, indicating that work motivation positively and significantly affects organizational citizenship behavior. However, the second hypothesis reveals that organizational commitment has a negative and statistically insignificant impact on organizational citizenship behavior. The study recommends that organizations actively engage employees in decision-making processes and ensure equal opportunities for all. Additionally, providing employee training programs to support career development is advised. A limitation of this research is its relatively small sample and population size. Future studies should consider incorporating additional variables that could affect motivation, commitment, and citizenship behavior.